Moral Disasters - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Sciences, 2013)
The present short review essay explores the definition of evilness contrasting three seminal works, Narrating Evil, a good book authored by Pia Lara, Lucifer effects in P. Zimbardo and Violence of S. Zizek. Although both texts represent contrasting view respecting to the moral disasters, what is important to discuss here is to what an extent, good people may act criminal acts. In former century, liberal theory postulated that evilness should be controlled in democratic countries. The law of people not only was sufficient to grant the individual liberties but also ensured the life of republic. This was nothing further from the truth.